(untitled) (Journal Of Educational and Psychological Researches, 2017)
This study focused on the various forms of violence that aged people encounter in their late life, the significance of taking measures that enhance not only the welfare for aged people but also the influence of early stage of life and how the old age effects on people experience throughout their live. Further, the importance of raising the awareness among communities to the extent of seriousness of old age in order to teach children the right habits and traditions, which are faded away over time. The researcher indicated that raising the avenues of collaboration among home members, social organization, and all governmental facilities will support and provide a good treatment for this group of people.